İRONİDEN KOMEDİYE BİR EĞLENCE ARACI: EFRÂSİYÂB’IN HİKÂYELERİ - (:unkn) unknown (My University, 2015)
İronie/irony teriminin kaynağı kabul edilen eirônia sözcüğü, Yunanca "bilmezden gelerek sormak" anlamına gelir. Gerçek ile görünüş arasındaki uyumsuzluğa işaret eden ironi, çoğunlukla eleştirel nitelik taşımaktadır. Yazar eleştirilerini ironi yoluyla iletirken eleştirinin dozunu yükseltebilir; ancak dilini yumuşatmış olur. İronik anlatımda, ifadeler daha vurucu ve sarsıcı hale geldiğinden okuyucu üzerinde daha etkili olurlar. İroni yöntemini kullanan yazarın asıl amacı, değersizleştirmek ya da küçük düşürmekten çok eleştiri nesnelerini olumlu anlamda değişim ve dönüşüme zorlamaktır. İroninin komikle benzer bir yanı vardır. Komik duygusu "bir şeyle o şeyin sunumu arasındaki uyumsuzluk"tan kaynaklandığı gibi, ironi de söylenen ile kastedilen arasındaki uyumsuzluktan kaynaklanır. Ayrıca komiğin de sosyal düzenleme gibi bir amacının olması onu ironiye yaklaştırır. İroninin iç içe geçtiği bir başka tür, parodidir; çünkü parodiler mutlaka ironi içerirler. Postmodern anlatının Türk Edebiyatındaki önemli temsilcilerinden biri olan İhsan Oktay Anar, eserlerinde ironiyi eleştirel nitelikleriyle başarıyla kullanan bir yazardır. Anar, Efrâsiyâb'ın Hikâyeleri adlı eserinde ironiyi hem bir eleştiri hem de eğlence aracı olarak kullanır. Bu yüzden hikâyelerde ironinin çoğunlukla komediyle yer yer de parodiyle iç içe geçtiği görülmektedir. Bu da ironinin ortaya çıkardığı gerilimi düşürmekte, hem yazarın hem de okuyucunun metinle buluşmasını eğlenceli hale getirmektedir. Hikâyelerin masal unsurlarıyla örülü olması da buna zemin hazırlamakta ve eğlence unsurunun öne çıkmasını kolaylaştırmaktadır. Yazar, eğitim sistemi, dini yaşantı, batıl inançlar, sözde kahramanlık, gelenek ve görenekler, erkek egemen toplum yapısı ve kadın-erkek ilişkilerini ironi nesnesi olarak seçer. İroni kurbanları da seçilen bu ironi nesneleriyle ilintili kişilerdir. Anar, hikâyelerinin ironik kurgusunda alazon-eiron karşıtlığından yararlanmaz. Bunun yerine yazar, eiron rolünü kendisi üstlenir. Bu çalışmada, ironinin komedi ve parodi öğeleriyle birleşerek İhsan Oktay Anar'ın Efrâsiyâb'ın Hikâyeleri (2013) adlı eserinde yazarve okuyucu açısından eğlence unsuruna dönüşmesi, örnekler üzerinden gösterilmektedir.

The word ironie/ irony which is accepted as the source of the word eironia which means "asking for something as pretending ignorant" in Greek. Irony which is a literary instrument that shows the inconsistency between real and appearance is mostly used as a criticism method. When author is transferring his criticisms by irony, he may increase the dose of criticism; but he would also soften his tone. In the ironic expression, due to the fact that expressions become more striking and shocking, they become more effective on the reader. The main purpose of the author who uses irony method is not to devalue or to humiliate but rather to force the criticism elements to change and transformation in the affirmative meaning. There are similar aspects of irony with comic. As well as the sense of comic stems from “the inconsistency between something and the presentation of it” irony also arises from “the inconsistency between said and intended”. In addition, comic has the objective of social arrangement and this makes it closer to the irony. Another genre intertwined with irony is parody; because parodies necessarily contain irony. İhsan Oktay Anar, who is one of the important representatives of the postmodern narrative in Turkish Literature, successfully uses comedy and parody with their critical features in his works. In this study, how irony and comedy factors in Efrâsiyâb’ın Hikâyeleri (Stories of Afrasiyab), written by İhsan Oktay Anar, turn into means of entertainment from the viewpoint of author and reader will be represented. Efrâsiyâb’ın Hikâyeleri(Stories of Afrasiyab), written by using "Frame narrative" technique, consists of nine chapters. In this study, the classification of examples is based on the differentiation of "irony object" and "irony victim" made by D.C. Muecke. İhsan Oktay Anar uses the irony as an instrument of both criticism and entertainment in Efrâsiyâb’ın Hikâyeleri (Stories of Afrasiyab). In the stories, it is seen that irony intertwines mostly with comedy and partly with parody. This reduces the tension posed by the irony, and also makes entertaining the meeting of text with author and reader. For this, a lot of elements of fairy tales in the story also prepares the ground and makes it easier for entertainment element to become prominent. Anar’s criticisms made by irony technique aren’t the criticisms of political incidents, people or a certain period. Anar, with the influence of his philosopher identity, mostly discusses thoughts and beliefs, settled social attitudes and habits and their reflections in social life. In this study, the most typical irony usages have been commentated as examples. On the other hand, the irony which has a dominant function in the structure of book is preponderant element in almost entire work. Irony technique, that criticizes while praising, provides a great convenience of expression to author. The author chooses educational system, religious life, the superstitions, the so-called heroism, customs and traditions, maledominated social structure and gender relations as the subject of irony. Irony victims are people associated with these selected irony objects. Although the contrast between eiron and alazon characters put forward by Aristotle, constitute the structure of ironic texts, Anar doesn’t benefit from alazon-eiron contrast in the ironic fiction of his stories. Instead of this, the author plays the role of eiron himself. Anar mostly creates the alazon characters which have the features such as unscrupulousness, selfishness, self-interest, ignorance, greed, biased and far from being inquisitive, lack of education, misinterpretation of religion. In the story titled “Güneşli Günler” (Sunny Days), main irony objects are the violent education given at schools; this education intended to frighten "pupils" and the teaching staff who continues to give such kind of education. Anar expands his critical view focused on a fictional example, as he does in other stories and draws attention to the corruptions in the education system and social perception. The headmaster nicknamed “Kont”(Count) and the deputy principal nicknamed “Sağır”(Deaf) are the irony victims. In the story, headmaster "Kont"(Count) has been fictionalized as a vampire drinking the blood of students. And it is extremely ironic that "Sağır"(Deaf), who is committing violence to students, is an art teacher. Anar’s one of the most important irony objects is the religious phenomenon. Within his criticisms on religious life or the clergy, the comedy elements seem to be used much with irony. The author makes a mockery of clergy or religious person character that he created. The author warns the society and aims to display in front of society the comic and tragic situations of those who use the religion for their comfort and establish authority on people and abuse pure feelings of people. In addition, some people uses the concepts of "prayer" , "pilgrimage ”, "angel", "sin", "reward" and social morality in order to get a clear conscience, gain social status and reputation, establish authority on others, this intention of them made in the eyes of the author to convert them as an irony object. "Wise old man” motif, that is seen in dreams and attributed religious meaning among people, is also taken place in Efrâsiyâb’ın Hikâyeleri (Stories of Afrasiyab), as an ironic object. In the story of “Bir Hac Ziyareti”(A Visit to Hajj), imams who are regarded as the symbol of authority and dignity by the people of Zengefil village; in "Dünya Tarihi"(World History) self-seeking sheikh of town bazaar and the town traders who are keen on worshipping but also very stingy; in the story titled "Şarap ve Ekmek"(Wine and Bread), the imam Sefa who is preaching at mosque on the day but drinking at a tavern at nights and Zeynelabidin who is selling religious books like prayer teacher book and parts of Quran, and is described as "religious" because of that; and in "Ezine Canavarı"(Ezine Monster), Nafile Kalf who is trying to gain a reputation by seeming honest and religious are ironic characters. Another irony object of him is the superstitions. The superstitions such as; blue bead worn against the evil eye, lead pouring, making husband eat donkey tongue in order to make him homebody, are criticized in an ironic and comic way. Town tradesmen in the story titled "Dünya Tarihi"(World History), and Ms. Hamiyet in the story titled "Ezine Canavarı"(Ezine Monster) form a basis for author’s irony with their attitudes and behaviors reflecting those beliefs. In "Dünya Tarihi"(World History), the attitudes of village people, who prepare to fight with thieves in the mountains and plays so-called hero, are told with inversion method of the concept of courage. In the story “Ezine Canavarı”(EzineMonster) Anar, emphasizes through “conservative town life “that values, customs and traditions are not questionable in small communities and this situation is a major obstacle for being an individual. Customs and traditions are another irony objects that Anar focuses on. Anar transfers his criticisms on social life to the reader with a sharp irony. In the story of "Ezine Canavarı"(Ezine Monster) Anar, "the conservative town life" through small community of people in prevailing values, to consist not questioning the customs and traditions and in front of that individual in this case emphasizes the not constitute a major obstacle. According to Anar, in this kind of communities to establish authority over the people and to scare them are easier. The best way of this intimidation is gossiping. Gossipers who are called by names like Maymun Saniye, Pullu Hayriye, Sansar Melahat, Aybaşı Neriman, Allı Mualla, Boncuklu Rabiş, are the irony victims who pose threat and fear in the town. Anar ironizes male-dominated society and male-female relationships through the social perception of women. In "Ezine Canavarı"(Ezine Monster), the measure for a woman as “a lady” and as “respected” in the eyes of society and her husband is close to the concept of “serve husband” by the writer this comprehension is used as irony in a funny way. The perception of Hamiyet and her four daughters in this matter is told ironically and their attitudes and behaviors are told in a comic way in the story. The attitudes and behaviors described in more funny language. Besides the way of life of Ayvaz Kasap and his four sons is important to demonstrate the attitudes and behaviors expected from men in the community. One of the methods that Anar uses to increase the power of his irony is the parody. Author refers to this method in his stories "Bidaz’ın Laneti" (Curse of Bidaz) and "Gökten Gelen Çocuk"(Child Coming from Sky). The legend of the Phrygian king Midas’ power to convert everything to gold is parodied in the story "Bidaz’ın Laneti"(Curse of Bidaz); and Clark Kent character known as "Superman" is parodied in the “Gökten Gelen Çocuk" (Child Coming from Sky). Galloğlu Hamdi whose mother-in-law transforms to gold in a treasure search adventure, and Gülerk Kent who falls from the sky to a garden of a house and is adopted by landlords are irony victims of these stories. Anar mostly adopts the inversion principle of irony in his stories. While the author is doing this, he severely criticizes the pressure of administrators in the education system, and also the pressure by means of religious elements, traditions and customs among people. He usually highlights the heroes in the story by their indifference and satisfaction towards the mistakes in the social life and interpersonal relationships. While doing this, author uses the most important instrument of irony which is telling serious cases as funny and telling something funny as serious. In addition, author put himself against the alazon characters as the eiron character and this function is strengthening the meaning. Efrâsiyâb’ın Hikâyeleri (Stories of Afrasiyab), not only entertains the readers with its narrative constructed by the combination of ironic, comic and parodic elements; but also gives the reader a ground for in-depth thinking and questioning on a lot of social issues.
AN ENTERTAINTMENT TOOL FROM IRONY TO COMEDY: EFRÂSİYÂB'IN HİKÂYELERİ